Pupuk Organik Cair plus Urine Kambing terhadap Pertumbuhan dan Hasil Kedelai Edamame Organik - Untung Santoso; Riza Adrianoor Saputra; Noni Septiana (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
The development of edamame soybeans is quite promising. Since edamame soybeans are an export commodity, increasing edamame soybean production can support domestic and international markets. Cultivating edamame soybeans has obstacles in every production process. The soil fertility level is the main factor in increasing the production of edamame soybean cultivation, but using soil chemicals is one of the causes of decreased fertility. The solution to these obstacles is to use organic fertilizer from waste materials, one of which is liquid organic fertilizer (LOF) from goat urine. This study aims to determine the effect of LOF+ goat urine on the growth and yield of organic edamame soybeans and the best concentration of LOF+ goat urine on the growth and yield of organic edamame soybeans. The research used a randomized block design (RBD) and five treatment levels of LOF+ goat urine: 0, 5, 10, 15, and 20%, with five repetitions to obtain 25 experimental units. The research showed that treatment LOF 5% (equivalent to 50 mL LOF+ in 950 mL water) was the best treatment for increasing edamame plant height by 23.03%, number of leaves by 12.59%, and number of fresh pods by 17.29%, weight of fresh pods 41.05%, and production of as much as 41% can increase the growth and yield of edamame soybeans.